2007
DOI: 10.1007/s11258-007-9290-0
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of pristine boreal forest floor community after selective removal of understorey, ground and humus layers

Abstract: In boreal spruce forests that rarely experience extensive disturbances, fine-scale vegetation gaps are important for succession dynamics and species diversity. We examined the community implications of fine-scale gap disturbances by selective removal of vegetation layers in a pristine boreal spruce forest in Northern Finland. The aim was to investigate how the speed of recovery depends on the type of disturbance and the species growth form. We also wanted to know if there appeared changes in species compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The observed data agree perfectly with results of other investigations concerning the influence of disturbance severity on colonization processes (Hautala et al 2001(Hautala et al , 2008Jonsson and Essen 1998;Mayer et al 2004;Peterson and Campbell 1993;Rydgren et al 2004;Skvortsova et al 1983). This phenomenon is most likely induced by the almost complete destruction of the soil bank of vegetative and generative diaspores of the soil bank after a severe disturbance, as the importance of soil bank in the processes of colonization is known to be very high (Jonsson and Essen 1998;Mayer et al 2004;Putz 1983;Rydgren et al 2004;Turner et al 1998).…”
Section: Peculiarities Of Species Richness Recovery After Disturbancesupporting
confidence: 92%
See 1 more Smart Citation
“…The observed data agree perfectly with results of other investigations concerning the influence of disturbance severity on colonization processes (Hautala et al 2001(Hautala et al , 2008Jonsson and Essen 1998;Mayer et al 2004;Peterson and Campbell 1993;Rydgren et al 2004;Skvortsova et al 1983). This phenomenon is most likely induced by the almost complete destruction of the soil bank of vegetative and generative diaspores of the soil bank after a severe disturbance, as the importance of soil bank in the processes of colonization is known to be very high (Jonsson and Essen 1998;Mayer et al 2004;Putz 1983;Rydgren et al 2004;Turner et al 1998).…”
Section: Peculiarities Of Species Richness Recovery After Disturbancesupporting
confidence: 92%
“…The majority of community resilience investigations have been carried out in grasslands (Lavorel 1999;McNaughton 1977;Tilman and Downing 1994;Whitford et al 1999; see also review Hooper et al 2005) or in forest ecosystems (Skvortsova et al 1983;Cooper-Ellis et al 1999;Hautala et al 2001Hautala et al , 2008Jonsson and Essen 1998;Mayer et al 2004;Peterson and Campbell 1993;Rydgren et al 2004), which had not been affected by atmospheric pollution. Meanwhile, environmental pollution is one of the most wide-ranging types of long-term anthropogenic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore do not consider the size of seeds to be the reason for the different occurrence of trees species, but we assume that the actual reasons are the specifically different microclimatic (temperature and humidity; Beatty, 1984;Peterson and Cambell, 1993), and the competitive (Kuuluvainen and Juntunen, 1998;Nakashizuka, 1989) and pathogenic (Simon et al, 2011) conditions of the microsites after seed germination and during tree growth. Tree mortality at an early age is surely influenced by the different chemical properties of the forest floor (Šamonil et al, 2008a), as well as by differences between decomposer communities (Beatty and Sholes, 1988;Hautala et al, 2008). Simon et al, 2011 thus found a lower density of seeds of F. sylvatica on the mounds compared with pits, but the mortality rate was so high that it eventually led to a significant absence of regeneration in the pit microsite; Harrington and Bluhm (2001) also pointed out the difference between tree growth rates on different microsites.…”
Section: Development Of Tree Species Populations On the Pit-moundsmentioning
confidence: 99%
“…Diaspore banks are potentially important in the maintenance of species diversity, influencing the development of forest floor species assemblages (van Tooren and During 1988;Jonsson and Esseen 1990;Rydgren et al 2004) and promoting secondary succession and site restoration (Grime 1989;Poschlod 1995;Rydgren et al 1998;Campbell et al 2003;Hautala et al 2008). Forest harvesting may affect the viability, composition, and germination of buried diaspores and, therefore, the future establishment of species.…”
Section: Introductionmentioning
confidence: 99%